Peningkatan Penanganan Ikan Hasil Tangkapan di Pelabuhan Perikanan Nusantara (PPN) Palabuhanratu - Nanda Sari; Ernani Lubis; Thomas Nugroho; Retno Muninggar; Mustaruddin Mustaruddin; Dwi Putra Yuwandana; Julia Eka Astarini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Handling fish caught after the fishing prosess is very important to do. Because it will affects the quality of the fish caught. Fish is a perishable product. So that the quality can drop dramatically if no handling of fish catches properly. The handling of fish caught is not only done while on the ship, but is carried out starting from the fish caught on the ship to the fish caught to the final consumer. Handling of fish caught in PPN Palabuhanratu has not been good and right for payang fisherman. Therefor an initial step is taken, for example through counselling to payang fisherman and fisheries businesess regarding the handling of fish catch that are good and right. Counselling that has been done was attend by people as many as 42 fisherman with payang fishing gear.